HUSBAND'S SUPPORT WITH ADHERENCE TO THE INJECTION SCHEDULE FOR MOTHERS - Lailatul Fadliyah; Danty Indra Puspitaningtyas; Amellia Mardhika; Anestasia Pangestu Mei Tyas; Emulliana Sulpat; Lestari Sudaryanti (Journal of Vocational Nursing, 2023)
Introduction: Contraception is a method or tool used to prevent pregnancy. Injectable contraception is a type of hormonal contraceptive method. Contraceptive failure is the main source of unwanted pregnancies, failures can be caused by a lack of support from the closest people. The study aimed to determine the relationship between husband's support and adherence to repeat contraceptive injections by mothers. Methods: This research is analytic research with a cross-sectional design. The study population was 219 couples of childbearing age who were injectable contraceptive acceptors. The sample technique is purposive sampling, with a total sample of 40 couples of childbearing age. For data collection techniques researchers use a questionnaire. The analytical test used is the Chi Square Test. Results: Results showed that 28 respondents received high support from their husbands (70%), and 33 respondents adhered to repeat injection contraceptive visits (82.5%). Results of bivariate analysis with Chi Square obtained p value = 0.000. Conclusions: There is a relationship between husband's support and compliance with injection contraceptive repeat visits. Health education is needed for the husband and family to support regular repeat visits to minimize the occurrence of contraceptive failure.